Seasonal dynamics of Sulfur dioxide and Sulfate aerosols over India: Insights from Sentinel-5P and MERRA-2 datasets - Priya J S; Krishnakumar V; Sabna Rahim (Bulletin of Atmospheric Science and Technology, 2026)

Aerosol and cloud characteristics during two extreme periods over Kerala - J. S. Priya; V. Krishnakumar (Meteorology and Atmospheric Physics, 2026)

Decline of Acropora spp. in the Saudi Waters of the Arabian Gulf: Insights from Thirteen Years of Reef Surveys - Sudhanshu Dixit; Reynaldo T. Lindo; Rommel H. Maneja; Ace Vincent B. Flandez; Jinoy Gopalan; Thiyagarajan Duraisamy; Goutham Sambath; Yasir Y. Asiri; Mubarak S. Al-Jedani; Periyadan K. Krishnakumar; Karuppasamy P. Manikandan; Thadickal V. Joydas; et al. (Ocean Science Journal, 2026)

Leaf-driven Nanotechnology: Eco-friendly Synthesis of Antibacterial Silver Nanoparticles Using Zingiber officinale leaf extract - Asha G; Krishnakumar V (Journal of Pharmaceutical Innovation, 2026)

Integrated assessment of the environmental stress and human health risks associated with potentially toxic elements in Ashtamudi estuarine sediments, India - Jeenu Jose; A. Krishnakumar; V. R. Adhipa; K. Anoop Krishnan (Environmental Geochemistry and Health, 2026)

Aflatoxin detection and quality assessment in dried red chilli (Capsicum annum L.): A multifaceted approach using physical, microstructural, and machine learning techniques - M. Balasubramaniyan; J. Shavani Durga; V. Chelladurai; T. Senthilkumar; T. Krishnakumar; G. Jeevarathinam (Journal of Stored Products Research, 2026)

BiOI-decorated g-C₃N₄ heterostructure photocatalyst for versatile environmental remediation in a column-type batch photoreactor under tunable conditions: Mechanistic insights, stability, reaction intermediates, and hazard profiling of the system - T. Abisheik; V. Pandiyan; Balakrishna Avula; Surya Chinnasamy; Krishnamoorthy Shanmugaraj; Gabriela Sandoval-Hevia; Govindasami Periyasami; Krishnakumar Balu (Journal of Water Process Engineering, 2026)

Rare-earth (Er3+) modified ZnO photocatalyst: Dual action in organic dye degradation under UV/solar light and microbial suppression - S. Sargunavathi; S. Balamurugan; Balakrishna Avula; T. Abisheik; N. Lakshman Kumar; V. Pandiyan; Vimalraj. V; Arun Thirumurugan; Gabriela Sandoval-Hevia; Abdullah K. Alanazi; Krishnakumar Balu (Journal of Water Process Engineering, 2026)

Exploring the anticancer potential of Tinospora cordifolia with computational insights into EGFR inhibition - G. Asha; S. Lekshmi; K.P. Najmathunnisa; T. Rajva; V. Krishnakumar; K. P. Safna Hussan (In Silico Pharmacology, 2025)

Modulation of COX-2, 5-LOX, and cytokine signalling by Carica papaya L. Leaf cultivar ‘Red Lady’ flavonoids in inflammation: in-vitro and in-silico insights - Sheethal S. Kumar; Chandran Remya; K. Krishnakumar; Evelyn Maria; K. V. Dileep; Mathew John (Natural Product Research, 2025)

Unveiling the potential of yttrium-modified ZnO nanoparticles in Reactive Red 120 dye breakdown and microbial inhibition - V. Mariyappillai; C. Shiyamala; M. Tiffany; T. Abisheik; V. Pandiyan; Krishnamoorthy Shanmugaraj; Gabriela Sandoval-Hevia; Govindasami Periyasami; Krishnakumar Balu (Journal of Water Process Engineering, 2025)

Energy management of energy hub with renewable energy resources based on GTOA-ACNN approach - R. Krishnakumar; U. Arun Kumar; V. Gomathy; N. A. Natraj (Environment, Development and Sustainability, 2025)

Drought Vulnerability Assessment Using GIS and Remote Sensing Techniques: A Case Study in Part of Coimbatore, Tamil Nadu, India - S. Krishnakumar; V. Sreevidhya; S. Vivek; V. Priya (Journal of the Indian Society of Remote Sensing, 2025)

Study on the Seasonal and Spatial Variations of Cirrus Parameters, Radiative Characteristics and Precipitation over the Indian Subcontinent - J. S. Priya; V. Krishnakumar; Sona Baiju; R. G. Sreelekshmi; Afna Shoufeer (Journal of the Indian Society of Remote Sensing, 2025)

Unveiling the ecological status of the Arabian Gulf's marine ecosystem: Insights from benthic community analysis - Paravanparambil Rajakumar Jayachandran; Thadickal V. Joydas; Angel Borja; Seerangan Manokaran; Javier Franco; Joxe Mikel Garmendia; Jayanath Gopi; Karuppasamy P. Manikandan; Mohamed Asharaf; Rommel H. Maneja; Ali M. Qasem; Hamed Alghamdi; et al. (Marine Pollution Bulletin, 2024)

Optimizing simultaneous energy management for slow- and fast-charging electric vehicles: a hybrid approach - Jayarama Pradeep; M. Vijayaragavan; V. Krishnakumar; B. Suresh Kumar (Clean Technologies and Environmental Policy, 2024)

Seasonal variability in trace metal concentrations in sediment samples from the Puducherry and Cuddalore coasts of Tamil Nadu, India - K. Sanjai Gandhi; D. Pradhap; S. Krishnakumar; V. Kanagaraj (Total Environment Advances, 2024)

Optimal battery-swapping mechanism for electric vehicles using hybrid approach - N. Madhanakkumar; M. Vijayaragavan; V. Krishnakumar; Kannan Palanisamy (Clean Technologies and Environmental Policy, 2024)

DRASTIC model developed with lineament density to map groundwater susceptibility: a case study in part of Coimbatore district, Tamilnadu, India - Krishnakumar Subramanian; V. Sreevidya; R. Venkatasubramani; Vivek Sivakumar (Environment, Development and Sustainability, 2023)

Ecological status of macrobenthic communities in the Saudi waters of the western Arabian Gulf - Thadickal V. Joydas; Mohammad A. Qurban; Angel Borja; Seerangan Manokaran; Karuppasamy P. Manikandan; Lotfi Jilani Rabaoui; Joxe Mikel Garmendia; T.T.M. Asharaf; Korhan Ayranci; Ahsan Mushir Shemsi; Shoeb Mohammed; Abdullajid U. Basali; et al. (Regional Studies in Marine Science, 2023)

Effectiveness of Site-Specific Management Practices on the Amelioration of Soil Acidity in the Coconut Growing Entisol and Ultisol of Humid Tropics - Jeena Mathew; A. Abdul Haris; S. Indhuja; V. Krishnakumar; K. M. Nair; Ravi Bhat; K. S. Anil Kumar (Journal of Soil Science and Plant Nutrition, 2022)

Monitoring of heavy metal contamination in Netravati river basin: overview of pollution indices and risk assessment - S. Gayathri; K. Anoop Krishnan; A. Krishnakumar; T. M. Vishnu Maya; Vinu V. Dev; Sibin Antony; V. Arun (Sustainable Water Resources Management, 2021)

First report on the association of ‘Candidatus Phytoplasma asteris’ with lethal wilt disease of coconut (Cocos nucifera L.) in India - Merin Babu; S. Thangeswari; A. Josephrajkumar; V. Krishnakumar; A. Karthikeyan; V. Selvamani; Mol Daliya; Vinayaka Hegde; H. P. Maheswarappa; Anitha Karun (Journal of General Plant Pathology, 2021)

Ocean Energy Systems Wave Energy Modelling Task: Modelling, Verification and Validation of Wave Energy Converters - Fabian Wendt; Kim Nielsen; Yi-Hsiang Yu; Harry Bingham; Claes Eskilsson; Morten Kramer; Aurélien Babarit; Tim Bunnik; Ronan Costello; Sarah Crowley; Benjamin Gendron; Giuseppe Giorgi; et al. (Journal of Marine Science and Engineering, 2019)
The International Energy Agency Technology Collaboration Programme for Ocean Energy Systems (OES) initiated the OES Wave Energy Conversion Modelling Task, which focused on the verification and validation of numerical models for simulating wave energy converters (WECs). The long-term goal is to assess the accuracy of and establish confidence in the use of numerical models used in design as well as power performance assessment of WECs. To establish this confidence, the authors used different existing computational modelling tools to simulate given tasks to identify uncertainties related to simulation methodologies: (i) linear potential flow methods; (ii) weakly nonlinear Froude–Krylov methods; and (iii) fully nonlinear methods (fully nonlinear potential flow and Navier–Stokes models). This article summarizes the code-to-code task and code-to-experiment task that have been performed so far in this project, with a focus on investigating the impact of different levels of nonlinearities in the numerical models. Two different WECs were studied and simulated. The first was a heaving semi-submerged sphere, where free-decay tests and both regular and irregular wave cases were investigated in a code-to-code comparison. The second case was a heaving float corresponding to a physical model tested in a wave tank. We considered radiation, diffraction, and regular wave cases and compared quantities, such as the WEC motion, power output and hydrodynamic loading.

Marine invertebrates colonizing a causeway in the Manifa offshore oilfield, Saudi Arabia - Diego Lozano-Cortés; Thadickal V. Joydas; Khaled Abdulkader; Periyadan K. Krishnakumar; Mohammad A. Qurban (Marine Biodiversity, 2019)

First record of the invasive Bondar’s nesting whitefly, Paraleyrodes bondari Peracchi on coconut from India - A. Josephrajkumar; Chandrika Mohan; Merin Babu; Arya Krishna; V. Krishnakumar; Vinayaka Hegde; P. Chowdappa (Phytoparasitica, 2019)

Discovery of a sooty mould scavenging beetle, Leiochrinus nilgirianus Kaszab (Coleoptera: Tenebrionidae) on coconut palms infested by the invasive rugose spiralling whitefly, Aleurodicus rugioperculatus Martin (Hemiptera: Aleyrodidae) - A. Josephrajkumar; Chandrika Mohan; J. Poorani; Merin Babu; Daliyamol; V. Krishnakumar; Vinayaka Hegde; P. Chowdappa (Phytoparasitica, 2018)

Macrobenthic Community Structure in the Northwestern Arabian Gulf, Twelve Years after the 1991 Oil Spill - Thadickal V. Joydas; Mohammad A. Qurban; Angel Borja; Periyadan K. Krishnakumar; Abdulaziz Al-Suwailem (Frontiers in Marine Science, 2017)

Role of lutoid membrane transport and protein synthesis in the regeneration mechanism of latex in different Hevea clones - S. Sreelatha; Sheela P. Simon; V. C. Mercykutty; Kavitha K. Mydin; R. Krishnakumar; K. Annamalainathan; James Jacob (Acta Physiologiae Plantarum, 2016)

Non-timber forest products certification and management: a socioeconomic study among the Kadars in Kerala, India - Jyotsna Krishnakumar; John F. Yanagida; V. Anitha; Rajeev Balakrishnan; Theodore J. K. Radovich (Environment, Development and Sustainability, 2015)

Antithyroid agents and QSAR studies: inhibition of lactoperoxidase-catalyzed iodination reaction by isochromene-1-thiones - M. V. Kirthana; F. Nawaz Khan; Ponnurengam Malliappan Sivakumar; Mukesh Doble; P. Manivel; K. Prabakaran; V. Krishnakumar (Medicinal Chemistry Research, 2013)

Report on the palm aphid, Cerataphis brasiliensis on ‘Kalparaksha’ coconut cultivar - A. Josephrajkumar; P. Rajan; Chandrika Mohan; V. Krishnakumar (Phytoparasitica, 2011)

Internal Tides in the Coastal Waters of NE Arabian Sea: Observations and Simulations - P. V. Hareesh Kumar; S. Lekshmi; P. S. V. Jagadeesh; K. Anilkumar; G. V. Krishnakumar; A. D. Rao (Marine Geodesy, 2010)

Identification, characterization and utilization of EST-derived genic microsatellite markers for genome analyses of coffee and related species - Ramesh K. Aggarwal; Prasad S. Hendre; Rajeev K. Varshney; Prasanna R. Bhat; V. Krishnakumar; Lalji Singh (Theoretical and Applied Genetics, 2007)

Production of Penicillin G acylase from Bacillus sp.: Effect of medium components - J. Rajendhran; V. Krishnakumar; P. Gunasekaran (World Journal of Microbiology and Biotechnology, 2003)